Формы глагола в списках Литовского статута 1529 г. - Влacoвa Т. П. (Kalbotyra, 1990)
The article investigates verb forms in the four manuscripts of the Lithuanian Statute of 1529 which are in Old Byelorussian. A comparative analysis of the divergent forms in these manuscripts is presented.